The prevalence and associated factors of psychological distress among adults in a suburban community in Johor, Malaysia - Ab Manan, Norhafizah; Abdalqader, Mohamed A.; Che Wan Ahmad Pauzi, Che Wan Mohammad Ashraf; Mahat, Nur Ain; Kyaw, Thin Mon; Sathik, Hassan Basri Jahubar; Khaing, Mya Sanda; Naing, Thein Win; Mohamad, Abd Rahim; Rampal, Krishna Gopal (Human Resource Management Academic Research Society, 2023)
Psychological distress refers to non-specific symptoms of stress, anxiety, and depression. Although it is common in the community, it is crucial to identify groups at risk of experiencing psychological distress for appropriate intervention strategies. This study aims to assess the prevalence of psychological distress and to determine the association between sociodemographic factors and satisfaction with life on psychological distress among adults in a community in Johor, Malaysia. A cross-sectional survey was conducted in October 2022 at a community residential area in Muar, Johor. Self-administered General Health Questionnaire (GHQ-12) and Satisfaction with Life Scale (SWLS) were used to measure psychological distress and satisfaction with life, respectively. Multiple logistic regression was utilized for the analysis with the significant level set at 5%. Out of 279 respondents, 36.2% (95% CI=36.2%, 42.0%) of them were having psychological distress. Younger age, Chinese, individuals with a primary education and those who were not satisfied with life were significantly associated with psychological distress. In summary, one-third of the population in the community reported psychological distress, with preponderance among certain groups of people. It is important to implement interventions effectively such as community activities in the target population to lower the psychological distress in the community.